Electrochemical Surface Restructuring of Phosphorus-Doped Carbon@MoP Electrocatalysts for Hydrogen Evolution - Jiang, Huimin; Yan, Liting; Zhang, Shuo; Zhao, Yanchao; Yang, Xue; Wang, Yameng; Shen, Jianxing; Zhao, Xuebo; Wang, Lianzhou (Nano-Micro Letters, 2021)
The hydrogen evolution reaction (HER) through electrocatalysis is promising for the production of clean hydrogen fuel. However, designing the structure of catalysts, controlling their electronic properties, and manipulating their catalytic sites are a significant challenge in this field. Here, we propose an electrochemical surface restructuring strategy to design synergistically interactive phosphorus-doped carbon@MoP electrocatalysts for the HER. A simple electrochemical cycling method is developed to tune the thickness of the carbon layers that cover on MoP core, which significantly influences HER performance. Experimental investigations and theoretical calculations indicate that the inactive surface carbon layers can be removed through electrochemical cycling, leading to a close bond between the MoP and a few layers of coated graphene. The electrons donated by the MoP core enhance the adhesion and electronegativity of the carbon layers; the negatively charged carbon layers act as an active surface. The electrochemically induced optimization of the surface/interface electronic structures in the electrocatalysts significantly promotes the HER. Using this strategy endows the catalyst with excellent activity in terms of the HER in both acidic and alkaline environments (current density of 10 mA cm−2 at low overpotentials, of 68 mV in 0.5 M H2SO4 and 67 mV in 1.0 M KOH). Highlights: 1 An electrochemical-induced surface restructuring strategy is developed to design phosphorus-doped carbon@MoP electrocatalysts which exhibits excellent activity for the hydrogen evolution reaction (HER) in both acidic and alkaline electrolytes. 2 The activation process and the fundamental mechanism of the prominent synergistic interaction between the phosphorus-doped carbon and MoP are elucidated.